Magnesium-based metal composite material and preparation method and application thereof
By forming magnesium-aluminum layered bimetallic hydroxide nanosheets on the surface of magnesium-based metal and depositing nanozirconia particles, the problem of magnesium-based metal degradation rate in the human body is solved, and its density and corrosion resistance are improved. Achieves low-cost and easy-to-produce biomedical implant materials.
Patent Information
- Application Number
- CN202411178876.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-27
AI Technical Summary
The degradation rate of magnesium-based metals in the human body is too fast, resulting in corrosion and biocompatibility problems. The existing surface protection methods have problems such as toxicity, high cost and poor density, making it difficult to widely use in biomedical implants.
Magnesium-aluminum layered bimetallic hydroxide nanosheets are used and nanozirconia particles are deposited on their surfaces. A dense film layer is formed through hydrothermal reaction and water bath reaction, which enhances the density and binding force of the film layer and reduces the risk of corrosion.
It improves the density and corrosion resistance of magnesium-based metal composite materials, enhances the bonding force between the film layer and the substrate, reduces the corrosion current density and peeling risks, is cheap and easy to mass production.
Smart Images

Figure CN119121012A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal material surface modification, and particularly relates to a magnesium-based metal composite material and a preparation method and application thereof. Background Art
[0002] Magnesium is an essential element in the human body and is directly related to many biological mechanisms and metabolic reactions. Magnesium and its alloys have excellent mechanical properties, biocompatibility and biodegradability, and are ideal biomedical materials. Compared with traditional bioceramics and polymers, magnesium-based metals not only have the conventional mechanical advantages of medical metal materials, but also have in vivo biodegradability and an elastic modulus that is more compatible with human bones. This feature reduces the stress shielding effect at the implant / bone interface and reduces the possibility of secondary injury, making it stand out among traditional medical metal materials. From a physiological point of view, magnesium-based metals degrade slightly by solidifying the adjacent tissues of the wound, which can avoid secondary surgery and infection risks. Compared with magnesium alloys, pure magnesium metal does not need to add other metal elements, which can avoid potential toxic substances from entering the human body, and has great application prospects in the field of biomedical materials. However, magnesium-based metals have poor corrosion resistance in the human body, resulting in a too fast degradation rate. The large amount of hydrogen produced by rapid corrosion and the substantial increase in the local pH value of body fluids can lead to blood flow obstruction, tissue necrosis and even death of patients. The short service life of magnesium-based metals and the negative effects they bring limit their widespread application in the field of biomedical implants. Therefore, controlling their degradation rate in human body fluids is the key to using medical magnesium as human implant materials.
[0003] At present, the strategy to slow down the corrosion rate of magnesium-based metals in the human body is mainly to construct surface protective coatings. Surface protective coatings can effectively regulate the degradation rate of magnesium-based metals in the human body, have better biosafety, and are cost-controlled, so they have received more attention. Common methods for constructing anti-corrosion films on the surface of magnesium-based metals include chemical conversion, anodizing, micro-arc oxidation, electroplating, electrophoresis, coating, etc.
[0004] Traditional chemical conversion treatment technology mainly uses hexavalent chromium ions to form a dense protective film on the surface of magnesium-based metals, which can effectively protect the substrate from corrosion. It is widely used due to its low cost and simple process. However, hexavalent chromium ions are toxic and highly carcinogenic, which seriously harms the ecological environment and human health. Most electrolytes in anodizing treatment also contain heavy metal elements such as chromium and manganese. Micro-arc oxidation, electroplating, and electrophoresis processes have safety and environmental protection issues such as high voltage, high temperature, and heavy metals in the electrolyte. In addition, the micro-arc oxidation film layer on the surface of magnesium-based metals has poor density, forming a porous structure, which is difficult to block the erosion of corrosive media. The polymer film prepared by the coating process has the problem of poor bonding between the coating and the substrate.
[0005] In recent years, the nanosheet-like double hydroxide film layer grown in situ on the surface of magnesium-based metals has attracted much attention due to its good physical barrier effect and ion exchange function, and has great application potential in the corrosion protection of magnesium alloys. However, due to the porous structure of the nanosheet and poor density, there is still a problem of insufficient corrosion protection performance. Some researchers have further sealed the pores by further covering the surface of the layered double hydroxide with a polymer film layer. Although the sealing effect is good, the simple coating forms a double-layer structure, which is very easy to peel off and difficult to apply in practice. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a magnesium-based metal composite material and a preparation method and application thereof, wherein the magnesium-based metal composite material has good density, strong film layer bonding force and good corrosion resistance.
[0007] In a first aspect, the present invention provides a magnesium-based metal composite material, comprising a magnesium-based metal and magnesium-aluminum layered double metal hydroxide nanosheets located on the surface of the magnesium-based metal, wherein the magnesium-aluminum layered double metal hydroxide nanosheets contain zirconium oxide.
[0008] In some embodiments of the present invention, the magnesium-based metal is a magnesium-based metal with a magnesium content of ≥ 99.99%.
[0009] In some embodiments of the present invention, the magnesium aluminum layered double hydroxide nanosheet is a single-layer structure.
[0010] In a second aspect of the present invention, a method for preparing the magnesium-based metal composite material according to the first aspect of the present invention is provided, comprising the following steps:
[0011] The magnesium-based metal and aluminum salt solution are mixed, subjected to a hydrothermal reaction, and magnesium-aluminum layered double hydroxide nanosheets are generated in situ, and then ion cleaning is performed to obtain a semi-finished product;
[0012] The semi-finished product is mixed with a fluorozirconate solution, reacted in a water bath to generate zirconium oxide, and thus a magnesium-based metal composite material is obtained.
[0013] In some embodiments of the present invention, the aluminum salt solution includes at least one of an aluminum nitrate solution, an aluminum chloride solution, and an aluminum sulfate solution.
[0014] In some embodiments of the present invention, the aluminum salt solution is an aluminum nitrate solution, and the concentration of the aluminum nitrate solution is 0.5-1.5mmol / L, for example, it can be any point value among 0.5mmol / L, 0.7mmol / L, 0.9mmol / L, 1.1mmol / L, 1.3mmol / L, 1.5mmol / L, or a range value between two arbitrary point values.
[0015] In some embodiments of the present invention, the mass ratio of the magnesium-based metal to the aluminum salt solution is 1:3 to 1:12, for example, it can be any point value among 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, or a range value between two arbitrary point values.
[0016] In some embodiments of the present invention, the pH of the hydrothermal reaction is 9-11, preferably 10; and / or the temperature of the hydrothermal reaction is 110-130°C, preferably 120°C; and / or the time of the hydrothermal reaction is 14-16h, preferably 15h.
[0017] In some embodiments of the present invention, during the hydrothermal reaction, aqueous ammonia is used to adjust the pH value.
[0018] In some embodiments of the present invention, before the hydrothermal reaction, the magnesium-based metal is further pretreated, and the pretreatment includes the steps of: gradually grinding the magnesium-based metal with 600-2000 mesh SiC sandpaper, and ultrasonically cleaning with water, anhydrous ethanol, and acetone after grinding, and drying.
[0019] In some embodiments of the present invention, the reflected power of the ion cleaning is 120-140W, preferably 130W; and / or the time of the ion cleaning is 5-60s, preferably 5-30s, more preferably 10-20s; and / or the atmosphere of the ion cleaning is an inert atmosphere.
[0020] In some embodiments of the present invention, the inert atmosphere is an argon atmosphere.
[0021] In some embodiments of the present invention, the fluorozirconate solution includes at least one of a potassium fluorozirconate solution, a sodium fluorozirconate solution, and an ammonium fluorozirconate solution.
[0022] In some embodiments of the present invention, the fluorozirconate solution is an ammonium fluorozirconate solution, and the concentration of the ammonium fluorozirconate solution is 0.5-1.5 mmol / L, for example, it can be any point value among 0.5 mmol / L, 0.7 mmol / L, 0.9 mmol / L, 1.1 mmol / L, 1.3 mmol / L, 1.5 mmol / L, or a range value between two arbitrary point values.
[0023] In some embodiments of the present invention, the mass ratio of the semi-finished product to the fluorozirconate solution is 1:2 to 1:10, for example, it can be any point value among 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, or a range value between two arbitrary point values.
[0024] In some embodiments of the present invention, the temperature of the water bath reaction is 50-70°C, preferably 60-70°C; and / or the time of the water bath reaction is 5-10 min, preferably 10 min.
[0025] The third aspect of the present invention provides use of the magnesium-based metal composite material described in the first aspect of the present invention in the preparation of a medical implant.
[0026] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0027] (1) The magnesium-based metal composite material provided by the present invention further densifies the magnesium-aluminum layered double hydroxide nanosheets by introducing zirconium oxide, thereby improving the density and corrosion resistance. At the same time, the bonding force between the magnesium-aluminum layered double hydroxide nanosheet film and the magnesium-based metal is strong and not easy to peel off.
[0028] (2) The present invention utilizes a low-temperature water bath process to deposit nano-zirconium oxide particles on the surface of magnesium-aluminum layered double hydroxide nanosheets to further densify the nanosheets. The magnesium-aluminum layered double hydroxide nanosheets fix the nano-zirconium oxide by mechanical riveting, which not only solves the problem of poor density of the magnesium-aluminum layered double hydroxide nanosheets, but also solves the problem of poor bonding strength of the directly deposited zirconium oxide film and the easy occurrence of cracks in the zirconium oxide film.
[0029] (3) The preparation method of the magnesium-based metal composite material of the present invention is low-cost, easy to mass-produce, and the product quality is controllable. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a surface scanning electron microscope test image of the magnesium-based metal composite material obtained in Example 1;
[0031] Figure 2 This is a surface scanning electron microscope test image of the magnesium-based metal composite material obtained in Example 2;
[0032] Figure 3 This is a surface scanning electron microscope test image of the magnesium-based metal composite material obtained in Example 3;
[0033] Figure 4 This is a surface scanning electron microscope test image of the magnesium-based metal composite material prepared in Comparative Example 1;
[0034] Figure 5 This is a surface scanning electron microscope test image of the magnesium-based metal composite material prepared in Comparative Example 2. DETAILED DESCRIPTION
[0035] The present invention is further described in detail below by specific examples. The raw materials, reagents or devices used in the examples can be obtained from conventional commercial sources or by prior art methods unless otherwise specified. Unless otherwise specified, the experiments or test methods are conventional methods in the art.
[0036] Example 1
[0037] A magnesium-based metal composite material is prepared by a preparation method comprising the following steps:
[0038] S1. The magnesium-based metal sheet is polished step by step using 600, 1200 and 2000 mesh SiC sandpaper, and then ultrasonically cleaned with deionized water, anhydrous ethanol and acetone respectively after polishing, and then dried in an oven at 45°C; wherein the magnesium content in the magnesium-based metal sheet is 99.99%;
[0039] S2, putting the magnesium-based metal sheet treated by S1 into a hydrothermal reactor containing 1mmol / L aluminum nitrate solution (ammonia water adjusted pH=10), wherein the mass ratio of the magnesium-based metal sheet to the aluminum nitrate solution is 1:4, the hydrothermal temperature is 120°C, the hydrothermal time is 15 hours, and the reaction is naturally cooled, taken out from the reactor, routinely cleaned, and then routinely ultrasonically cleaned with deionized water, anhydrous ethanol, and acetone, respectively, and dried in an oven at 45°C;
[0040] S3, placing the magnesium-based metal sheet treated in S2 into a plasma cleaning machine for activation treatment, with a reflection power of 130W, a time of 20s, and an argon atmosphere to obtain a semi-finished product;
[0041] S4. Immediately place the semi-finished product obtained in S3 into a 1mmol / L ammonium fluorozirconate solution in a water bath, wherein the mass ratio of the semi-finished product to the ammonium fluorozirconate solution is 1:2, the water bath temperature is 50°C, the time is 5 minutes, take it out of the water bath and let it stand for 10 minutes, clean it with deionized water, anhydrous ethanol, and acetone respectively, and dry it in an oven at 45°C to obtain a magnesium-based metal composite material.
[0042] The magnesium-based metal composite material prepared in Example 1 was tested using a scanning electron microscope. The surface scanning electron microscope test image is as follows: Figure 1 As shown. Figure 1 It can be seen that the film layer of the magnesium-based metal composite material prepared in Example 1 has slightly poor density and no cracks, which can meet the use requirements.
[0043] Example 2
[0044] A magnesium-based metal composite material is prepared by a preparation method comprising the following steps:
[0045] S1. The magnesium-based metal sheet is polished step by step using 600, 1200 and 2000 mesh SiC sandpaper, and then ultrasonically cleaned with deionized water, anhydrous ethanol and acetone respectively after polishing, and then dried in an oven at 45°C; wherein the magnesium content in the magnesium-based metal sheet is 99.99%;
[0046] S2, putting the magnesium-based metal sheet treated by S1 into a hydrothermal reactor containing 1mmol / L aluminum nitrate solution (ammonia water adjusted pH=10), wherein the mass ratio of the magnesium-based metal sheet to the aluminum nitrate solution is 1:4, the hydrothermal temperature is 120°C, the hydrothermal time is 15 hours, and the reaction is naturally cooled, taken out from the reactor, routinely cleaned, and then routinely ultrasonically cleaned with deionized water, anhydrous ethanol, and acetone, respectively, and dried in an oven at 45°C;
[0047] S3, placing the magnesium-based metal sheet treated in S2 into a plasma cleaning machine for activation treatment, with a reflection power of 130W, a time of 20s, and an argon atmosphere to obtain a semi-finished product;
[0048] S4. Immediately place the semi-finished product obtained in S3 into a 1mmol / L ammonium fluorozirconate solution in a water bath, wherein the mass ratio of the semi-finished product to the ammonium fluorozirconate solution is 1:2, the water bath temperature is 60°C, the time is 5 minutes, take it out of the water bath and let it stand for 10 minutes, clean it with deionized water, anhydrous ethanol and acetone respectively, and dry it in an oven at 45°C to obtain a magnesium-based metal composite material.
[0049] The magnesium-based metal composite material prepared in Example 2 was tested using a scanning electron microscope. The surface scanning electron microscope test image is as follows: Figure 2 As shown. Figure 2 It can be seen that the film layer of the magnesium-based metal composite material prepared in Example 2 has good density and no cracks.
[0050] Example 3
[0051] A magnesium-based metal composite material is prepared by a preparation method comprising the following steps:
[0052] S1. The magnesium-based metal sheet is polished step by step using 600, 1200 and 2000 mesh SiC sandpaper, and then ultrasonically cleaned with deionized water, anhydrous ethanol and acetone respectively after polishing, and then dried in an oven at 45°C; wherein the magnesium content in the magnesium-based metal sheet is 99.99%;
[0053] S2, putting the magnesium-based metal sheet treated by S1 into a hydrothermal reactor containing 1mmol / L aluminum nitrate solution (ammonia water adjusted pH=10), wherein the mass ratio of the magnesium-based metal sheet to the aluminum nitrate solution is 1:4, the hydrothermal temperature is 120°C, the hydrothermal time is 15 hours, and the reaction is naturally cooled, taken out from the reactor, routinely cleaned, and then routinely ultrasonically cleaned with deionized water, anhydrous ethanol, and acetone, respectively, and dried in an oven at 45°C;
[0054] S3, placing the magnesium-based metal sheet treated in S2 into a plasma cleaning machine for activation treatment, with a reflection power of 130W, a time of 20s, and an argon atmosphere to obtain a semi-finished product;
[0055] S4. Immediately place the semi-finished product obtained in S3 into a 1mmol / L ammonium fluorozirconate solution in a water bath, wherein the mass ratio of the semi-finished product to the ammonium fluorozirconate solution is 1:2, the water bath temperature is 60°C, and the time is 10 min. After taking it out of the water bath, let it stand for 10 min, and clean it with deionized water, anhydrous ethanol, and acetone respectively by conventional ultrasonic cleaning, and dry it in an oven at 45°C to obtain a magnesium-based metal composite material.
[0056] The magnesium-based metal composite material prepared in Example 3 was tested using a scanning electron microscope. The surface scanning electron microscope test image is as follows: Figure 3 As shown. Figure 3 It can be seen that the film layer of the magnesium-based metal composite material prepared in Example 3 has excellent density and no cracks.
[0057] Example 4
[0058] A magnesium-based metal composite material is prepared by a preparation method comprising the following steps:
[0059] S1. The magnesium-based metal sheet is polished step by step using 600, 1200 and 2000 mesh SiC sandpaper, and then ultrasonically cleaned with deionized water, anhydrous ethanol and acetone respectively after polishing, and then dried in an oven at 45°C; wherein the magnesium content in the magnesium-based metal sheet is 99.99%;
[0060] S2, putting the magnesium-based metal sheet treated by S1 into a hydrothermal reactor containing 1mmol / L aluminum nitrate solution (ammonia water adjusted pH=10), wherein the mass ratio of the magnesium-based metal sheet to the aluminum nitrate solution is 1:7, the hydrothermal temperature is 120°C, the hydrothermal time is 15 hours, and the reaction is naturally cooled, taken out from the reactor, routinely cleaned, and then routinely ultrasonically cleaned with deionized water, anhydrous ethanol, and acetone, respectively, and dried in an oven at 45°C;
[0061] S3, placing the magnesium-based metal sheet treated in S2 into a plasma cleaning machine for activation treatment, with a reflection power of 130W, a time of 5s, and an argon atmosphere, to obtain a semi-finished product;
[0062] S4. Immediately place the semi-finished product obtained in S3 into a 1mmol / L ammonium fluorozirconate solution in a water bath, wherein the mass ratio of the semi-finished product to the ammonium fluorozirconate solution is 1:8, the water bath temperature is 60°C, and the time is 10 min. After taking it out of the water bath, let it stand for 10 min, and clean it with deionized water, anhydrous ethanol, and acetone respectively by conventional ultrasonic cleaning, and dry it in an oven at 45°C to obtain a magnesium-based metal composite material.
[0063] The film layer of the magnesium-based metal composite material prepared in Example 4 has excellent density and no cracks.
[0064] Example 5
[0065] A magnesium-based metal composite material is prepared by a preparation method comprising the following steps:
[0066] S1. The magnesium-based metal sheet is polished step by step using 600, 1200 and 2000 mesh SiC sandpaper, and then ultrasonically cleaned with deionized water, anhydrous ethanol and acetone respectively after polishing, and then dried in an oven at 45°C; wherein the magnesium content in the magnesium-based metal sheet is 99.99%;
[0067] S2, putting the magnesium-based metal sheet treated by S1 into a hydrothermal reactor containing 1mmol / L aluminum nitrate solution (adjusted with ammonia water to pH=10), wherein the mass ratio of the magnesium-based metal sheet to the aluminum nitrate solution is 1:8, the hydrothermal temperature is 120°C, the hydrothermal time is 15 hours, and the reaction is naturally cooled, taken out from the reactor, routinely cleaned, and then routinely ultrasonically cleaned with deionized water, anhydrous ethanol, and acetone, respectively, and dried in an oven at 45°C;
[0068] S3, placing the magnesium-based metal sheet treated in S2 into a plasma cleaning machine for activation treatment, with a reflection power of 130W, a time of 40s, and an argon atmosphere to obtain a semi-finished product;
[0069] S4. Immediately place the semi-finished product obtained in S3 into a 1mmol / L ammonium fluorozirconate solution in a water bath, wherein the mass ratio of the semi-finished product to the ammonium fluorozirconate solution is 1:10, the water bath temperature is 60°C, the time is 10 min, take it out from the water bath and let it stand for 10 min, clean it with deionized water, anhydrous ethanol and acetone by conventional ultrasonic cleaning, and dry it in an oven at 45°C to obtain a magnesium-based metal composite material.
[0070] The film layer density of the magnesium-based metal composite material obtained in Example 5 is slightly poor, has no cracks, and can meet the use requirements.
[0071] Comparative Example 1
[0072] The only difference from Example 3 is that Comparative Example 1 is prepared by using steps S1 and S2 without ion cleaning and water bath reaction.
[0073] The magnesium-based metal composite material prepared in Comparative Example 1 was tested using a scanning electron microscope. The surface scanning electron microscope test image thereof is shown in FIG. Figure 4 As shown. Figure 4 It can be seen that although the film layer of the magnesium-based metal composite material prepared in Comparative Example 1 has no cracks, its density is very poor and cannot meet the use requirements.
[0074] Comparative Example 2
[0075] The only difference from Example 3 is that, in Comparative Example 2, the water bath time in step S4 is adjusted to 20 min.
[0076] The magnesium-based metal composite material prepared in Comparative Example 2 was tested using a scanning electron microscope. The scanning electron microscope test image of the surface is shown in FIG. Figure 5 As shown. Figure 5 It can be seen that the film layer of the magnesium-based metal composite material prepared in Comparative Example 2 has very poor density and cracks.
[0077] Comparative Example 3
[0078] The only difference from Example 3 is that the magnesium-based metal sheet of Comparative Example 3 is AZ31 magnesium alloy (magnesium content <99.99%).
[0079] The film layer of the magnesium-based metal composite material prepared in Comparative Example 3 has very poor density and cracks.
[0080] Product performance testing
[0081] The magnesium-based metal composite materials prepared in Examples 1-5 and Comparative Examples 1-3 were used as test samples and the following tests were performed.
[0082] (1) Electrochemical test: The film layer was measured using the Tafel curve test. The test was conducted in a three-electrode system, which consisted of a rectangular platinum counter electrode, a saturated calomel electrode as a reference electrode, and a working electrode exposed to a 1 cm area. The working electrode was immersed in SBF simulated body fluid. The corrosion current density was obtained using the cathode extrapolation method. The lower the corrosion current density value, the better the corrosion resistance.
[0083] (2) Film bonding strength test: Select a suitable fixture and use the peeling fixture to fix the sample on the electronic universal testing machine. Start the electronic universal testing machine, select the peeling test mode, apply the peeling force between the film layer and the substrate, gradually increase the load until the film layer peels off, and record the load value at which the damage occurs.
[0084] The test results are shown in Table 1.
[0085] Table 1
[0086]
[0087] It can be seen from Table 1 that the corrosion current density of the magnesium-based metal composite materials prepared in Examples 1-5 is significantly lower than that in Comparative Examples 1-3, indicating that the products of the embodiments of the present invention have better compactness and significantly better corrosion resistance.
[0088] Compared with other embodiments, Example 3 optimizes the preparation process parameters, and the comprehensive performance of the product obtained is further improved.
[0089] The preferred embodiments of the present invention are specifically described above, but the invention is not limited to the embodiments. Those skilled in the art may make various equivalent modifications or substitutions without violating the spirit of the invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.
Claims
1. A magnesium-based metal composite material, It is characterized in that The magnesium-based metal composite material comprises a magnesium-based metal and magnesium-aluminum layered double metal hydroxide nanosheets located on the surface of the magnesium-based metal, wherein the magnesium-aluminum layered double metal hydroxide nanosheets contain zirconium oxide.
2. The magnesium-based metal composite material according to claim 1, It is characterized in that The magnesium-based metal is a magnesium-based metal with a magnesium content of ≥99.99%.
3. The magnesium-based metal composite material according to claim 1, It is characterized in that The magnesium-aluminum layered double metal hydroxide nanosheet is a single-layer structure.
4. The method for preparing the magnesium-based metal composite material according to any one of claims 1 to 3, It is characterized in that The following steps are involved: The magnesium-based metal and aluminum salt solution are mixed, subjected to a hydrothermal reaction, and magnesium-aluminum layered double hydroxide nanosheets are generated in situ, and then ion cleaning is performed to obtain a semi-finished product; The semi-finished product is mixed with a fluorozirconate solution, reacted in a water bath to generate zirconium oxide, and thus a magnesium-based metal composite material is obtained.
5. The preparation method according to claim 4, It is characterized in that The aluminum salt solution includes at least one of an aluminum nitrate solution, an aluminum chloride solution and an aluminum sulfate solution.
6. The preparation method according to claim 4, It is characterized in that The pH of the hydrothermal reaction is 9-11; and / or, the temperature of the hydrothermal reaction is 110-130° C.; and / or, the time of the hydrothermal reaction is 14-16 hours.
7. The preparation method according to claim 4, It is characterized in that The reflected power of the ion cleaning is 120-140W; And / or, the ion cleaning time is 5-60s; and / or, the ion cleaning atmosphere is an inert atmosphere.
8. The preparation method according to claim 4, It is characterized in that The fluorozirconate solution includes at least one of a potassium fluorozirconate solution, a sodium fluorozirconate solution and an ammonium fluorozirconate solution.
9. The preparation method according to claim 4, It is characterized in that The temperature of the water bath reaction is 50-70° C.; and / or the time of the water bath reaction is 5-10 min.
10. Use of the magnesium-based metal composite material according to any one of claims 1 to 3 in the preparation of medical implants.
Citation Information
Patent Citations
Non-impurity-phase Mg-Al LDH coating on surface of magnesium alloy and preparation method and application thereof
CN110724946A
Magnesium alloy surface zirconia-based film and preparation method
CN112899664A
Magnesium oxide filler for compounding in resin and heat-conductive resin composition containing the same
JP2007070608A
The platinum catalyst impregnated on Hydrotalcite structure of 8B transition metal-magnesium-aluminum oxide as a carrier and preparation method thereof
KR1020130115885A
